Effects of fuel decomposition and stratification on the forced ignition of a static flammable mixture. Issue 5 (29th July 2021) - Chen, Xinyi; Peng, Wenrui; Gillard, Philippe; Courty, Leo; Sankhe, Mamadou Lamine; Bernard, Stephane; Wu, Yun; Wang, Yuan; Chen, Zheng
Abstract : In advanced propulsion systems such as scramjet engines, endothermic decomposition of onboard large hydrocarbon fuels can be used effectively for cooling and active thermal protection. During the cooling process, large hydrocarbon fuels absorb heat and decompose into small fragments. Since fuel decomposition changes the chemical and transport properties of the reactants, it is expected to affect the combustion afterwards. In this study, forced ignition in quiescent n-decane/air mixtures with fuel decomposition is investigated via a simplified model and transient numerical simulations considering detailed chemistry and transport. The emphasis is placed on assessing the effects of fuel decomposition on ignition kernel development and minimum ignition energy (MIE) in both homogenous and fuel-stratified mixtures. Fuel decomposition is modelled by a homogeneous ignition process in n-decane/air mixture at constant atmospheric pressure and with an initial temperature of 1300 K. Small fragments appear during the pyrolysis process. The partially-reacted mixture is frozen and cooled to a lower temperature and used as the initial mixture in forced ignition. For homogeneous mixtures, fuel decomposition can greatly promote ignition for fuel-lean decane/air mixtures while it has little effect for the stoichiometric case. Fuel decomposition also affects the duration of unsteady ignition kernel transition. Besides, fuel decomposition and fuel stratification are combined to further promote forced ignition. New flame regimes are observed and an optimum stratification radius is identified. In order to promote the forced ignition, only the fuel within the optimum stratification radius needs to be decomposed. Furthermore, laser and spark ignition experiments are conducted to measure the MIE of n-decane/ethylene/air mixtures with different equivalence ratios and ethylene blending ratios. The MIE measured in experiments cannot be directly compared with simulation results since the simulation model for forced-ignition is simplified. Nevertheless, the experimental results are consistent with simulation results and thus validate some conclusions mentioned above. The present results provide useful guidance to the fundamental understanding of forced ignition in a mixture with fuel decomposition.